Nurses’ intention to care of COVID-19 patients in hospitals dedicated to infectious disease in South Korea: application of the theory of planned behavior and verification of the moderating effect of ethical nursing competence - Mo, Mira; Moon, Seongmi; Song, Eun Kyeung (BMC nursing, 2024)
Background The theory of planned behavior is a conceptual framework of recent studies to identify and explain nurses’ intentions to care for patients with emerging infectious diseases. However, correlations between behavioral intentions and variables that explain them have been inconsistent in previous studies. The influence of new variables might be considered in this case. This study aimed to determine moderating effects of ethical nursing competence on nurses’ intention to care for COVID-19 patients in hospitals dedicated to infectious diseases based on the theory of planned behavior. Methods A cross-sectional survey was conducted. Data on intention to care for COVID-19 patients, perceived behavioral control, attitude toward the behavior, subjective norm, and ethical nursing competence were obtained from 190 nurses in three hospitals dedicated to infectious diseases in South Korea. The moderating effect of ethical nursing competence was analyzed using model I of PROCESS Macro. Ethical considerations: This study was approved by the Institutional Review Board of Ulsan University Hospital, South Korea. Written informed consent was obtained from each subject. Results The ethical nursing competence was a significant moderator in the relation between perceived behavioral control and the intention to care (B = 0.36, t = 2.16, p = 0.032). Ethical nursing competence did not have a significant interaction with attitude toward behavior or subjective norm. Conclusions This study showed that the higher the ethical nursing competence level, the greater the effect of perceived behavioral control on nurses’ intention to care for COVID-19 patients. Promoting ethical nursing competence is necessary for nurses who would take care of patients at the frontline of the infectious disease pandemic. Nursing managers should include ethical nursing competence in the assessment of nurses’ competence and design educational programs to enhance ethical nursing competence for efficient nursing staffing during a pandemic.